2021
DOI: 10.1186/s13765-020-00571-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stability of chia seed oil and flax seed oil and impact of rosemary (Rosmarinus officinalis L.) and garlic (Allium cepa L.) extracts on the prevention of lipid oxidation

Abstract: Chia seed and flax seed oils are rich in polyunsaturated fatty acids, but are susceptible to oxidative deterioration. The aim of this study was to determine the oxidative stability of chia seed and flax seed oils and enhance the stability using rosemary or garlic extracts. During accelerated storage at 65 °C for 14 days, the antioxidant abilities of rosemary or garlic extracts were evaluated and compared with those of butylated hydroxy toluene, ascorbyl palmitate, and α-tocopherol using peroxide value, conjuga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…The results of the work indicated that the coating with a rosemary extract showed bacteriolitic activity against S. aureus. The presence of phenol diterpens, carnosol or carnasoic acid [12,13] in the rosemary extract could be the cause of the complete inhibition in the growth the bacterium. The most likely antibacterial action mechanisms of these compounds were efflux pump inhibition or bacterial cell membrane and an increase in cell wall permeability [28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of the work indicated that the coating with a rosemary extract showed bacteriolitic activity against S. aureus. The presence of phenol diterpens, carnosol or carnasoic acid [12,13] in the rosemary extract could be the cause of the complete inhibition in the growth the bacterium. The most likely antibacterial action mechanisms of these compounds were efflux pump inhibition or bacterial cell membrane and an increase in cell wall permeability [28].…”
Section: Discussionmentioning
confidence: 99%
“…These mixtures contain active substances from both extracts. The rosemary extract should include ursolic acid [12,13] and the raspberry extract should contain tannins [16]. Alvarez-Martínez et al [28] proved that tannins and ursolic acid revealed multifactorial activity, rather than one activity mechanism, with pleiotropic effects at various levels also being observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Totally, except T0, FFAs content in cold-pressed sesame oil treatments was lower than Codex Alimentarius standards (Acid value: 4.0 mg KOH/g Oil), so we deduced that Senjed peel aqueous extract as a potential natural active ingredient, can improve the shelf life of oils and fats. Previously, Hussain et al (2018); Iqbal & Bhanger (2007); Elaigwu et al (2019), Jung et al (2021), andShahid et al (2018) also claimed that antioxidant activity of sesame seed extracts, garlic extracts, leaf extracts of Neem, rosemary and garlic, and cinnamon extract exhibited the comparable reduction effect on FFA contents in different oil as compared with synthetic antioxidant.…”
Section: Thermal Stability Of Senjed Peel Aqueous Extractsmentioning
confidence: 94%